Interpretation Of Women's Character In Modern Uzbek Storytelling (Based On Isajan Sultan's Stories "Turmush", "Beautiful") - Sadullayeva Muxlisa Xamrayevna (Global Scientific Publishing, 2023)
This article classified the portrayal of women in modern Uzbek stories. The pictures showing the character, attitude to life, and thoughts of an Uzbek woman were analyzed. The common aspects and peculiarities of Uzbek women in the stories of Isajon Sultan were contextually analyzed. The characteristics of these images, which are relevant for today's women, were explained.
Keywords: Contextual analysis; immanent analysis; artistic image